2022
DOI: 10.3390/nano12121971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Varying Concentrations of Silver Nanoparticles on the Fluoride Uptake and Recharge of Glass Ionomer Cement

Abstract: This study aimed to compare the amount of fluoride uptake and the recharge and release characteristics of conventional glass ionomer cement (GIC) without any additives in comparison to conventional glass ionomer cement supplemented with silver nanoparticles (AgNPs) at two concentrations: 0.1% and 0.2% (w/w). A total of 60 specimens were used in this in vitro study. The sample was divided into six groups—including three groups without fluoride charge: Group 1 (conventional GIC), Group 2 (GIC with 0.1% silver na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This was the case both before and after the discovery of antibiotics. Ag possesses a wide variety of advantageous qualities, one of which is potent “antimicrobial” activity against a wide variety of infectious diseases [ 83 ]. In recent decades, there has been a steady increase in the prevalence of antibiotic-resistant bacteria, which presents a threat to the usefulness of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case both before and after the discovery of antibiotics. Ag possesses a wide variety of advantageous qualities, one of which is potent “antimicrobial” activity against a wide variety of infectious diseases [ 83 ]. In recent decades, there has been a steady increase in the prevalence of antibiotic-resistant bacteria, which presents a threat to the usefulness of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incorporation of silver nanoparticles into glass ionomer cement (GIC) offers advantages in terms of antimicrobial properties and caries prevention, some studies have shown a notable adverse impact on the release of fluoride. This situation may place clinicians in a position where they need to strike a balance between harnessing the antimicrobial benefits of SNs and preserving the remineralization advantages of fluoride; it is advisable to conduct additional studies [2]. However, it is worth noting that the combined usage of silver nanoparticles (Ag NPs) with various dental materials did not compromise the biocompatibility of these materials.…”
Section: Silver-based Biomaterials In Conservative Dentistry and Endo...mentioning
confidence: 99%
“…Silver-reinforced GIC material can release both fluoride and silver ions [ 31 ]. However, ion release studies have demonstrated that these materials can only release low levels of silver ions, with a compromised fluoride release [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%